Cellular Effects of T-2 Toxin on Primary Hepatic Cell Culture Models of Chickens - Máté Mackei; Kata Orbán; Andor Molnár; László Pál; Károly Dublecz; Ferenc Husvéth; Zsuzsanna Neogrády; Gábor Mátis (Toxins, 2020)
Trichothecene mycotoxins such as T-2 toxin cause severe problems for agriculture, as well as for veterinary medicine. As liver is one of the key organs in metabolism, the main aim of our study was to investigate the immunomodulatory and cytotoxic effects of T-2 toxin, using primary hepatocyte mono-culture and hepatocyte—nonparenchymal cell (predominantly Kupffer cell) co-culture models of chicken. Cultures were exposed to 10 (T10 group), 100 (T100 group) and 1000 (T1000 group) nmol/L T-2 toxin treatment for 8 or 24 h. Alterations of cellular metabolic activity, the production of reactive oxygen species (extracellular H2O2), heat shock protein 70 (HSP70), and the concentration of different inflammatory cytokines such as interleukin (IL-)6 and IL-8 were investigated. Metabolic activity was intensely decreased by T-2 toxin administration in all of the cell culture models, in every applied concentration and incubation time. Concentrations of HSP70 and IL-8 were significantly increased in hepatocyte mono-cultures exposed to higher T-2 toxin levels (both in T100 and T1000 groups for HSP70 and in T1000 group for IL-8, respectively) compared to controls after 24 h incubation. Similarly, IL-6 levels were also significantly elevated in the T100 and T1000 groups in both of mono- and co-cultures, but only after 8 h of incubation time. In spite of the general harmful effects of T-2 toxin treatment, no significant differences were observed on reactive oxygen species production. Furthermore, the two cell culture models showed different levels of H2O2, HSP70, and IL-8 concentrations independently of T-2 toxin supplementation. In conclusion, the established primary cell cultures derived from chicken proved to be proper models to study the specific molecular effects caused by T-2 toxin. Metabolic activity and immune status of the different examined cell cultures were intensively affected; however, no changes were found in H2O2 levels.